Delicious! [compact disc, unabridged] : a novel - Reichl, Ruth (Random House Audio, 2014)
Billie Breslin has traveled far from her California home to take a job at Delicious, the most iconic food magazine in New York and, thus, the world. When the publication is suddenly shut down, the colorful staff, who have become an extended family for Billie, must pick up their lives and move on. Not Billie, though. She is offered a new job: staying behind in the magazine's deserted downtown mansion offices to uphold the Delicious Guarantee, a public relations hotline for complaints and recipes.